Establishment of In vitro Adventitious Root Cultures and Analysis of Flavonoids in Rumex crispus (Plant Tissue Culture and Biotechnology, 2015)
Adventitious root culture of leaf explants of R. crispus was established using different MS supplemented with different concentrations of auxins and a combination of NAA and Kn for growth and flavonoids production. Among the different auxins, NAA was more effective than IAA to induce adventitious roots. Adventitious roots grown on MS containing 5 ?M NAA and 0.5 ?M Kn showed the highest root growth, as well as the highest amount of total flavonoids (= 6) as compared with roots grown in other media. Chromatographic purification of the root extract showed that flavonoid composition also was influenced by hormone combinations in the culture media. The addition of Kn to the medium reduced or suppressed myricetin (M) and naringenin (N) production. Quercetin (Q) was not found in media containing Kn alone similar to the control medium. Isorhamnetin (I), kaempferol (K) and rutin (R) were produced in the roots on media supplemented with all hormone combinations, but were absent in 0.1 ?M Kn supplemented media similar to the control roots.Plant Tissue Cult. & Biotech. 25(1): 63-70, 2015 (June)